Acute tonsillitis in children: nuances in differential diagnosis - Vladimir K. Tatochenko (LLC "MEDIAFORMAT", 2021)
Currently, acute tonsillitis remains the most prevalent pediatric respiratory disease. The disease most often occurs in children up to 4 years of age, and in children of this age it is exclusively a viral disease; the viral tonsillitis contribution in older children is 60-80%. However, despite these figures, survey of physicians and parents, as well as audit indicate that the rate of prescribing antibiotics to children with acute tonsillitis is 90-95%, which means that the majority of children receive unnecessary antibiotic therapy. Appropriate differential diagnosis of the diseases, involv-ing the pharynx and tonsils, is a top priority for practicing otolaryngologists and pediatricians. The paper reports rare clinical cases of parapharyngeal abscess, adenoviral tonsillitis, infectious mononucleosis, PFAPA syndrome.